Identification Of Creative Economy Marketing Strategies After The Covid-19 Pandemic Disruption - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Asep Saepullah; Abdul Samad Arief; Juliana (Enrichment : Journal of Management, 2022)
Looking for various strategies to market the creative economy after a pandemic disruption is the best practice in running a business. Many studies have been conducted regarding one species during a pandemic, but few have led to the identification of post-pandemic strategies. This aticle was looking for some strategic business marketing strategy after pandemic. Therefore, the authors have collected some data from various publications or secondary data. Then we examine it under a phenomenological approach whose aim is to obtain some phenomenal relevant data to answer the discussion of this article, such as coding the data, evaluating the data, and concluding as desired. Get answers to research questions. Based on the existing data and the discussion of relevant topics, we can conclude that the strategies we have obtained include, among others, formulating products and prices for consumers. Furthermore, we try to maximize promotions with various strategies. Some are through social networking; some are paid media ads. A marketing system via email, then internet-based marketing, as well as direct sales strategies and strategies to identify product weaknesses and many methods that we believe are relevant for marketing strategies business after the pandemic. Thus, these findings will be useful material for further studies.